2020
DOI: 10.1159/000505924
|View full text |Cite
|
Sign up to set email alerts
|

Which Staging System Is More Suitable for Gastric Neuroendocrine Cancer and Mixed Adenoneuroendocrine Carcinomas? A Multicenter Cohort Study

Abstract: <b><i>Purpose:</i></b> To evaluate whether the European Neuroendocrine Tumor Society (ENETS) system or the 8th American Joint Committee on Cancer (AJCC) staging manual are suitable for gastric neuroendocrine carcinomas and/or mixed adenoneuroendocrine carcinomas (G-NECs/MANECs). <b><i>Methods:</i></b> Patients in a multicentric series with G-NEC/MANEC who underwent curative-intent surgical resection for a primary tumor were included. An optimal staging system was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Two propensity score models were generated for pairwise comparisons JAMA Network Open | Gastroenterology and Hepatology (including gastric neuroendocrine carcinoma vs gastric adenocarcinoma and gastric mixed adenoneuroendocrine carcinoma vs gastric adenocarcinoma). Tumor staging is an important pathological factor associated with the prognosis of gastric neuroendocrine carcinoma, gastric mixed adenoneuroendocrine carcinoma, and gastric adenocarcinoma, 22,23 while age and sex are common clinical factors associated with the prognosis of a tumor. 24,25 Thus, propensity scores were calculated using a logistic regression model, including pathological TNM stage, age, and sex, for all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two propensity score models were generated for pairwise comparisons JAMA Network Open | Gastroenterology and Hepatology (including gastric neuroendocrine carcinoma vs gastric adenocarcinoma and gastric mixed adenoneuroendocrine carcinoma vs gastric adenocarcinoma). Tumor staging is an important pathological factor associated with the prognosis of gastric neuroendocrine carcinoma, gastric mixed adenoneuroendocrine carcinoma, and gastric adenocarcinoma, 22,23 while age and sex are common clinical factors associated with the prognosis of a tumor. 24,25 Thus, propensity scores were calculated using a logistic regression model, including pathological TNM stage, age, and sex, for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…1). In terms of treatment, compared with patients with gastric adenocarcinoma, the proportion of total gastrectomy in patients with gastric neuroendocrine carcinoma or gastric mixed adenoneuroendocrine carcinoma was higher (1457 patients [52.3%] vs 291 patients [57.9%] and 231 patients [57.6%]; P < .001), but the number of lymph nodes retrieved was lower (median [IQR], 33 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] nodes vs 21 [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] nodes and 22 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: Discussionmentioning
confidence: 99%
“…Both Lin et al . 7 and van der Veen A et al . 8 found that there was no statistically significant difference in prognosis between gastric MiNEN and gastric NEC patients, but La Rosa et al .…”
Section: Introductionmentioning
confidence: 98%
“…La Rosa et al 6 reported that patients with GI MiNENs generally had a better prognosis than patients with NECs. Both Lin et al 7 and van der Veen A et al 8 found that there was no statistically significant difference in prognosis between gastric MiNEN and gastric NEC patients, but La Rosa et al 9 observed that gastric MiNEN has a better median overall survival (OS) than patients with pure NECs. As for the colon, the results are also varied.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Another relevant study on gNEC found that compared to the 8th AJCC TNM staging system, the 6th AJCC staging system was more suitable for gNEC. 12 These studies illustrated that the 8th AJCC TNM staging system could not stratify patients with gNENs. Since the 8th AJCC TNM staging system has limitations in stratifying patients with gNENs, and at the same time, gNENs with different tumor grades and characteristics have different prognoses and treatments, 1 , 13 a more robust staging system is needed to accurately predict the prognosis of gNENs patients and assist clinical therapeutic decisions.…”
Section: Introductionmentioning
confidence: 99%